mGluR5-mediated astrocytes hyperactivity in the anterior cingulate cortex contributes to neuropathic pain in male mice - Weida Shen; Fujian Chen; Yejiao Tang; Yulu Zhao; Linjing Zhu; Liyang Xiang; Li Ning; Wen Zhou; Yiran Chen; Liangxue Wang; Jing Li; Hui Huang; et al. (Communications Biology)
Abstract Astrocytes regulate synaptic transmission in healthy and pathological conditions, but their involvement in modulating synaptic transmission in chronic pain is unknown. Our study demonstrates that astrocytes in the anterior cingulate cortex (ACC) exhibit abnormal calcium signals and induce the release of glutamate in male mice. This leads to an elevation in extracellular glutamate concentration, activation of presynaptic kainate receptors, and an increase in synaptic transmission following neuropathic pain. We discovered that the abnormal calcium signals are caused by the reappearance of metabotropic glutamate receptor type 5 (mGluR5) in astrocytes in male mice. Importantly, when we specifically inhibit the Gq pathway using iβARK and reduce the expression of mGluR5 in astrocytes through shRNA, we observe a restoration of astrocytic calcium activity, normalization of synaptic transmission and extracellular concentration of glutamate, and improvement in mechanical allodynia in male mice. Furthermore, the activation of astrocytes through chemogenetics results in an overabundance of excitatory synaptic transmission, exacerbating mechanical allodynia in mice with neuropathic pain, but not in sham-operated male mice. In summary, our findings suggest that the abnormal calcium signaling in astrocytes, mediated by mGluR5, plays a crucial role in enhancing synaptic transmission in ACC and contributing to mechanical allodynia in male mice.